OP0178 Analysis of b-cells subsets in first degree relatives of patients with systemic lupus erythematosus. (12th June 2018) - Ruiz Roman, A.; Muñoz Jimenez, A.; Lucena, J.M.; Montes Cano, M.A.; Sanchez Sanchez, B.; Garrido Puñal, N.; Blanco Alonso, E.; Gil, R.; Quijada Carrera, J.; Rubio Romero, E.; Povedano Gomez, J.
Abstract : Background: Systemic lupus erythematosus (SLE) is an autoimmune, multiorgan disease characterised by periods of activity and remission. In lupus, one of the fields that has most helped his knowledge is the study of lymphocyte subpopulations through flow cytometry. Specifically, in the SLE some alterations have been detected at the level of B lymphocytes as the increase of B-cells subsets such as plasmablasts, plasma cells, transitional cells. There are no studies to date that have analysed the behaviour of B cells subsets in first -degree relatives of patients affected by lupus Objectives: To analyse if there quantitative difference in the B-cells subsets of the first-degree relatives of SLE with respect to the control population (healthy) and the lupus population Methods: Transversal descriptive study. We included 13 patients diagnosed with SLE according to the criteria of the American College of Rheumatology (ACR) with positivity for antinuclear antibodies (ANA) and anti-DNA, 34 first-degree relatives and 50 healthy controls between the months of May 2016 and March 2017. None of the subjects evaluated received treatment with rituximab or belimumab. We analysed B-cells subsets (negative double, naïve B-cells, unswitched memory B-cells, switched memory B-cells) in all the subjects included in our study. The 95% confidence intervals were obtained for both the means and the percentage difference. The level of statistical significance was established at p<0.05. The data was analysed with IBM SPSS software Statistics 19 and EPIDAT 4.1. Results: 47 subjects were analysed between relatives and patients, of which 33 (70.20%) were women. 13 subjects (27.70%) were diagnosed with lupus. 100% of those diagnosed with lupus were women. The mean (X) and confidence intervals (95% CI) for the different subgroups (healthy subjects, subjects diagnosed with SLE, relatives of the first degree) is shown in table 1. In none of the subpopulations analysed in patients diagnosed with SLE in front of relatives of 1 st grade it has reached statistical significance. When analysing B cells subsets of the three groups of subjects, we did find statistically significant differences between unswitched memory B cells of healthy subjects and 1 st degree relatives (being lower in the group of healthy subjects) This finding has not been described in any previous study, although it should be noted that the sample before us is small. Conclusions: There are quantitative differences between unswitched memory B-cells of healthy subjects and relatives of 1 st grade of SLE. More studies with a larger sample size are necessary to see the behaviour of the rest of B-type lymphocyte subpopulations Disclosure of Interest: None declared